Association between food insecurity and access to a mental health professional: cross-sectional analysis of NHANES 2007-2014 - Nina Camille Burruss; Marina Girgis; Karen Elizabeth Green; Lingyi Lu; Deepak Palakshappa (BMC, 2021)
Abstract Background To determine if individuals with food insecurity (FI) were less likely to have seen a mental health professional (MHP) within the past year than individuals without FI. Methods This is a cross-sectional analysis of data from the National Health and Nutrition Examination Survey (NHANES) conducted in the United States between 2007 and 2014. All participants 20 years of age or older were eligible for this study. We excluded participants who were pregnant, missing FI data, or missing data from the Patient Health Questionnaire (PHQ-9). The primary outcome was self-reported contact with a MHP in the past 12 months. We used multivariable logistic regression models to test the association between FI and contact with a MHP, controlling for all demographic and clinical covariates. Results Of the 19,789 participants, 13.9% were food insecure and 8.1% had major depressive disorder (MDD). In bivariate analysis, participants with FI were significantly more likely to have MDD (5.3% vs 2.8%, p < 0.0001) and to have been seen by a MHP in the preceding 12 months (14.0% vs 6.9%, p < 0.0001). In multivariable models, adults with FI had higher odds of having seen a MHP (OR = 1.32, CI: 1.07, 1.64). Conclusions This study demonstrates that individuals with FI were significantly more likely to have seen a MHP in the preceding 12 months compared to individuals without FI. Given the growing interest in addressing unmet social needs in healthcare settings, this data suggests that visits with MHPs may be a valuable opportunity to screen for and intervene on FI.